2005
DOI: 10.1101/lm.86205
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal muscimol shifts learning strategy in gonadally intact young adult female rats

Abstract: Learning strategy preferences depend upon circulating estrogen levels, with enhanced hippocampus-sensitive place learning coinciding with elevated estrogen levels. The effects of estrogen on strategy may be mediated by fluctuations in GABAergic function, given that inhibitory tone in the hippocampus is low when estrogen is high. We investigated the effects on learning strategy of intrahippocampal injections of a GABA A agonist in gonadally intact female rats. On the day of training, rats received 0.3 µL intrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 78 publications
5
28
0
Order By: Relevance
“…Korol and colleagues (2005) also found that directly inhibiting the hippocampus leads to rats shifting to striatal response learning or memory, with the most dramatic shift observed in proestrus rats [155]. Additionally, injecting E2 directly into the hippocampus enhances place memory whereas injecting it directly into the dorsal striatum impairs response memory We have also demonstrated that DA plays a role in E2's effect on multiple memory system bias.…”
Section: Hormones Reproductive Experience and Multiple Memory Systemsmentioning
confidence: 65%
“…Korol and colleagues (2005) also found that directly inhibiting the hippocampus leads to rats shifting to striatal response learning or memory, with the most dramatic shift observed in proestrus rats [155]. Additionally, injecting E2 directly into the hippocampus enhances place memory whereas injecting it directly into the dorsal striatum impairs response memory We have also demonstrated that DA plays a role in E2's effect on multiple memory system bias.…”
Section: Hormones Reproductive Experience and Multiple Memory Systemsmentioning
confidence: 65%
“…Probably the most worrisome aspect of the estrogen and learning literature is the meager effects that are often reported. Suffice to say, the effects reported by McElroy and Korol (2005) are robust, including those in response to hippocampal inhibition. The females in proestrus are probably most illustrious, since they demonstrate the most dramatic switch in choice as their hippocampus is inhibited.…”
mentioning
confidence: 95%
“…This is not to say that the results are inaccurate as reported, but rather that estrogen's effects are many and certainly not confined by human notions of good and bad. That said, the results from McElroy and Korol (2005) are unambiguous-as estrogen levels decrease from proestrus to estrus, the likelihood of using a place strategy decreases from ∼65% to less than half of that (28%). Meanwhile, as estrogen levels increase from estrus to proestrus, the use of the response strategy decreases from ∼75% to less than half of that (33%).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…An emerging theory proposes that estradiol modulates cognitive performance via shifts in learning strategy (Korol and Kolo 2002;Daniel and Lee 2004;Korol 2004;McElroy and Korol 2005;Zurkovsky et al 2007). Shifts in strategy use occurred across the estrus cycle in rats such that the hippocampus-dependent strategy was favored when estradiol levels were high .…”
mentioning
confidence: 99%